2020
DOI: 10.1101/2020.05.29.20110098
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evolutionary trends of the COVID-19 epidemic and effectiveness of government interventions in Nigeria: A data-driven analysis

Abstract: Background: Nigeria became the first sub Saharan African country to record a case of COVID-19 after an imported case from Italy was confirmed on February 27, 2020. Moving averages and the Epidemic Evaluation Indices (EEI) are two important but complementary methods useful in monitoring epidemic trends, they can also serve as a useful guide for policy makers and inform the timing of decisions on preventive measures. The objectives of this paper are to graphically depict the trends of new COVID-19 cases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…( Odukoya et al 2020 ) Lagos state was the first state to record and manage that case and has remained the epicentre of the pandemic, accounting for 36% of the cases and 22% of deaths as at July 26, 2020. (NCDC 2020, Odukoya et al 2020 )…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…( Odukoya et al 2020 ) Lagos state was the first state to record and manage that case and has remained the epicentre of the pandemic, accounting for 36% of the cases and 22% of deaths as at July 26, 2020. (NCDC 2020, Odukoya et al 2020 )…”
Section: Introductionmentioning
confidence: 99%
“…Since the discovery of the index case of COVID-19 in Nigeria in February 2020,(NCDC Coronavirus COVID-19 Microsite, 2020 the spread of the virus has increased exponentially due to communitybased human-to-human transmission. (Odukoya et al, 2020) Lagos state was the first state to record and manage that case and has remained the epicentre of the pandemic, accounting for 36% of the cases and 22% of deaths as at July 26, 2020. (NCDC 2020, Odukoya et al, 2020 COVID-19 is a novel disease with seemingly variable clinical presentation and progression.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lockdown policies initiated in Lagos, Nigeria, likewise had a strong impact in slowing down COVID-19 incidences, as the rise in the rate of new cases was reduced by a factor of 0.65. 8 Analysis of China's early response to the pandemic demonstrates the tension between the federal power concentration and local governance during the early phases of the epidemic, which led to a breakdown of their public health model and created a time lag between federal, regional, and local responses. 9 Although some countries have managed to control the pandemic better than others by prioritizing certain control measures, COVID-19 is still present in almost every part of the world and continues to cripple nations such as India.…”
Section: Introductionmentioning
confidence: 99%
“…In achieving this goal, the PTF has begun with vital steps such as primary and secondary prevention of man-to-man transmission; provision of isolation and quarantine centers, diagnostic and laboratory facilities; and carrying of researches to highlight relevant factors, interventions, and effects of these. For example, particular research showed that the rate of growth before the lockdown was high, but the lockdown reduced that growth by a factor of 0.65 which suggests policy effect (Odukoya et al , 2020). Given their data, the authors suggested that the epidemic evaluation index was still above 1.0 showing that the epidemic was still ongoing.…”
Section: Introductionmentioning
confidence: 99%